1966
DOI: 10.1063/1.1707972
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography of Poly-p-Xylylene

Abstract: Poly-p-xylylene prepared by the vapor-phase pyrolysis of di-p-xylylene affords a linear high-purity polymer whose crystalline transitions were characterized by x-ray and electron diffraction, mechanical creep studies, and differential thermal analysis (DTA). Two of the three endotherms observed by DTA correspond to the known alpha and beta polymorphs of poly-p-xylylene. The third, occurring at 270°C, is a reversible transition which is regarded as a smectic mesomorphic transition of the stable beta modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…[23] This approach takes advantage of the fact that poly(pxylylenes) are often semicrystalline polymers with characteristic features in the XRD spectra. [24,25] phous in the as-deposited state. [26] However, after annealing for 14 h at 120°C, the trifluoroacetyl-functionalized polymer 4 showed characteristic diffraction patterns, which likely correspond to (020) and (110) planes, and a d-spacing greater than that reported for the monoclinic poly(p-xylylene).…”
mentioning
confidence: 99%
“…[23] This approach takes advantage of the fact that poly(pxylylenes) are often semicrystalline polymers with characteristic features in the XRD spectra. [24,25] phous in the as-deposited state. [26] However, after annealing for 14 h at 120°C, the trifluoroacetyl-functionalized polymer 4 showed characteristic diffraction patterns, which likely correspond to (020) and (110) planes, and a d-spacing greater than that reported for the monoclinic poly(p-xylylene).…”
mentioning
confidence: 99%
“…This process yields a more highly crystalline polymer which clearly shows a third polymorph initially described as a smectic mesopmorph of the fl phase. 3 The p state was then renamed p1 and the highertemperature polymorph was designated as &. Thus the crystalline phase transformations were described as follows with the approximate transition temperatures: a -pl fl, -melt (followed by decomposition)…”
Section: Introductionmentioning
confidence: 99%
“…[36,28] Interestingly, the planar texture of the films is retained during the a to b 1 phase transition. The a to b 1 phase transition was first observed by Niegisch, who suggested that this transition is irreversible [37]. However, it was shown in Refs.…”
Section: Resultsmentioning
confidence: 96%